Comparison of Barriers Against Mammography Screening in Socioeconomically Very Low and Very High Populations - (:unkn) unknown (CUREUS INC, 2016)
Aim To compare barriers against mammography screening (MS) in socioeconomically the most and the least developed cities in a developing country, Turkey. Methods We compared two population-based survey studies investigating barriers against MS in women aged 40-69 years and living in the lowest socioeconomic status (SES) city (Mus) and the highest SES city (Istanbul/Bahcesehir). Results In Mus 2,054 and in Bahcesehir 908 women were surveyed. MS rate was higher in Bahcesehir (49% vs. 35%, p<0.001). Being younger than 50 years old and having no insurance were barriers against MS in Mus. Being older than 60 years of age, widowhood, being illiterate, unemployment, a monthly income lower than the hunger threshold and limited insurance coverage were barriers against MS in Bahcesehir. Both in Mus and in Bahcesehir women not reading the daily newspaper and not making annual gynecology visits had lower MS rates. Both in Mus and in Bahcesehir audiovisual media was the most common source of information about breast cancer (BC). Women, who had a chance to be informed about BC by their doctors, had a higher MS rate. Being knowledgeable about BC being the most common cancer in females increased MS rates in both cities, while a false belief of MS exposing to unnecessary radiation decreased MS rates in both cities. Conclusion Both in high and low SES populations more efforts should be given to influence women with low educational level, low-income level, and having no/limited insurance, while designing BC awareness programs. Low SES populations women being in 40-49 years age interval, in high SES populations being in 60-69 years age interval, and widowhood were SES-specific barriers and should be taken into consideration. Audiovisual media should be used efficiently to educate women on BC. Physicians from all specialties should not miss the chance to refer their patients to MS.
Keywords: breast cancer; socioeconomical status; mammography screening; prevention; population based; cross sectional; BREAST SELF-EXAMINATION; CANCER PATIENTS; WOMEN; ADHERENCE; RELATIVES; BELIEFS; AGE